Teachers' Obstacles in Implementing Numbered Head Together in Social Science Learning - Harini Widyaningtyas; Retno Winarni; Tri Murwaningsih (Institute of Advanced Engineering and Science, 2018)
This study is aimed at describing teachers’ obstacles in applying Numbered Head Together learning model in social science learning. The type of research is qualitative descriptive. The subject of the research is the third-grade teacher of elementary school in Sukoharjo Sub-district. The findings of the research were analyzed using interactive analysis of Miles and Huberman and were presented through descriptive narrative technique. The results reveal several obstacles that were experienced by the teachers. First, the time is limited. Second, the classroom atmosphere is noisy due to large number of students. Third, the number of students in total is not even. Fourth, the students interfere each other. Fifth, not all of the students work in the group. Sixth, the students are not actively responding. Seventh, the students are lack of confidence in the presentation.